Musique et référentialité sur les titres des disques Blue Note - Philippe Carrard (Cahiers de Narratologie)
The titles on the jackets of the records of the label Blue Note can denote the musical content of the album (Boogie-Woogie Classics), connote it (Blue Hour), or function strictly as indexes (Speak No Evil). Whatever their exact value might be, those titles make it possible to revisit a problem frequently raised in semiotics and musicology: the problem of knowing whether music « refers », and to what exactly. The question is especially acute in the case of some of the records released by Blue Note in the1960s, whose titles (It’s Time, Right Now, Let Freedom Ring) may refer to musical structures or to the situation of African-Americans in American sociey, which have both to be changed in the sense of more freedom.